Differential Prevalence and Dominant Species of Intestinal Protozoan Infections in Children versus Adults in a Refugee Setting, Eastern Chad - محمد أحمد فكي عبد الكريم; أ.د. أحمد عبد الله عجب الدور (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Intestinal protozoa represent the primary health challenge caused by poor water quality in vulnerable refugee settings. This study aimed to conduct a detailed analysis of the differential prevalence and dominant species of intestinal protozoa by age group among 4,023 refugees in Ouaddaï, Eastern Chad, spanning the period 2020–2024. Methods: Stool samples were examined microscopically using direct and concentration techniques. Demographic data were collected, and participants were categorized into four distinct age groups. The Chi-square test was used to determine the statistical significance of the association between age categories and infection positivity. Results: The overall prevalence of protozoa reached 79.65% of all recorded infections, confirming their epidemiological dominance. Differential analysis revealed a highly significant association between infection and age (P < 0.001). The 0–10 years (Children) age group recorded the highest overall parasite prevalence at 48.5%, significantly higher than the 30.0% observed in adult groups. Qualitatively, Entamoeba coli was the most prevalent protozoan overall. However, children showed the highest prevalence of the pathogenic species, Entamoeba histolytica, accounting for 28.3% of all protozoan infections within their specific group, indicating a heightened exposure to invasive species. Conclusion: The differential protozoan prevalence confirms that children (0–10 years) constitute the epidemiological core in Ouaddaï camps and are the group most vulnerable to severe clinical outcomes. This necessitates an urgent redirection of health and preventive interventions, prioritizing structural investment in Water, Sanitation, and Hygiene (WASH) to mitigate fecal contamination impacting this age group.